2000
DOI: 10.1080/713654960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of luteinising-hormonein vivoon ovarian cell subpopulations of newly-hatched chicks

Abstract: 1. We analysed the number and size of different ovarian cell subpopulations of newly-hatched chicks by ovarian cell suspension count and morphometric/stereological methods as well as delta5-3beta-hydroxysteroid dehydrogenase (delta5-3beta HSD) activity in these cells treated in vivo with LH during embryonic development. 2. Fertile White Leghorn eggs received 1 microg LH applied to the chorioallantoic membrane on days 13, 15, and 17 of incubation. All animals were killed within 24 h after hatching, the left ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The present findings and previous reports show that interstitial cells of the left ovary from newly hatched chick and theca cells are steroidogenic and target cells of estrogen (Narbaitz & De Robertis 1968, Davidson et al 1979, Gonza´lez-Mora´n & Calderon 2000.…”
Section: (B) Ovarian Cortex -Germinal Epithelium Cells (Ge) and Clustsupporting
confidence: 86%
See 1 more Smart Citation
“…The present findings and previous reports show that interstitial cells of the left ovary from newly hatched chick and theca cells are steroidogenic and target cells of estrogen (Narbaitz & De Robertis 1968, Davidson et al 1979, Gonza´lez-Mora´n & Calderon 2000.…”
Section: (B) Ovarian Cortex -Germinal Epithelium Cells (Ge) and Clustsupporting
confidence: 86%
“…These interstitial cells are clearly identified in the left ovary of the newly hatched chick, forming cell clusters with abundant cytoplasmatic lipid droplets, and a positive reaction for D5-3bHSD activity has been detected in these cell groups (Gonza´lez-Mora´n & Calderon 2000). Samar et al (1983) identified interstitial cells in the right medullary ovary of the chick embryo, with the same characteristics and positive reaction for D5-3bHSD as the left ovary.…”
Section: (B) Ovarian Cortex -Germinal Epithelium Cells (Ge) and Clustmentioning
confidence: 97%
“…It is noteworthy to mention that our observations indicate that the total volume of interstitial cells is the dominant component in the right ovary (55%) of 4‐week‐old chickens; cell hypertrophy is mainly responsible for the increase of total volume of interstitial cells. Previous works have detected a positive reaction for Δ5‐3βHSD activity in interstitial cells in the left and right ovaries of chicken embryo and newly hatched chicken (Narbaitz and Kolodny,1964; Scheib and Haffen,1967; Samar et al,1983; González‐Morán and Calderon,2000), confirming the steroidogenic function of these cells in both ovaries. Other authors have indicated that the left and right ovaries of the chicken embryo secrete steroid hormones and respond to gonadotropins with an increase in cyclic AMP concentration and in 17β‐estradiol and testosterone production (Teng and Teng,1977,1979; Teng et al,1982); both left and right medulla express aromatase and produce estrogens (Nakabayashi et al,1998; Endo et al,2007), and ERα is expressed symmetrically in both sides of the medulla (Andrews et al,1997; Smith et al,1997), but, in a previous work, we demonstrated a cell‐specific localization of ERα in the cortex and medulla of left and right ovaries (González‐Morán,2005).…”
Section: Discussionmentioning
confidence: 53%
“…The number of interstitial cells per left and right ovaries, volume of the individual interstitial cell, and volume of the nucleus and cytoplasm of interstitial cells were determined according to González‐Morán (1997) and González‐Morán and Calderon (2000).…”
Section: Methodsmentioning
confidence: 99%
“…It was hypothesized that these responses were due to a paracrine (local) mechanism versus systemic endocrine feedback. Additionally, medullary cells of newly hatched chickens respond to equine LH by increasing their size and 3b-HSD activity, but not by cellular proliferation (Gonzalez-Moran and Calderon, 2000). In vitro dispersed cell cultures of left embryonic chicken ovary, treated with FSH, increased cell proliferation in later stages of incubation and estrogen and testosterone synthesis in all stages of incubation studied (Pedernera et al, 1999).…”
Section: Discussionmentioning
confidence: 93%